A study on clinical and pathological correlation of benign breast lesions - Ramesh, Koorapati; Bookya, Kishan (International Surgery Journal, 2017)
Background: Benign breast diseases are common in females among young age group. Most common presentation is painless lump in the breast. Clinical and pathological correlation is essential. Fibroadenoma is the commonest among all other benign breast diseases. The aim was to study the age distribution of benign breast diseases. To study different types of benign breast diseases, their mode of clinical presentation and to correlate with radiological examination, cytology and histopathology of breast diseases. Methods: This was a prospective study conducted in the outpatient department of General Surgery in MGM hospital, Kakatiya Medical College, Warangal over a period of 2 years. A total of 250 patients diagnosed as benign breast diseases on clinical examination were studied and clinical findings were correlated with radiological, cytological and histopathological findings. Results: Patient age ranged 11 to 59 years. Majority of cases 150 (60%) were among 21-30 years. There were 98.8% female patients. Fibroadenomas were 57.6%, fibrocystic disease cases were 13.2%, breast abscesses were 1.6%, Intraductal papilloms 2.0%, simple cysts were 4.8%, Galactoceles 1.8%, Benign phyllodes were 3.6%, proliferative breast disease without atypia were 5.2% and gynaecomastia were 1.2% cases. Conclusions: Benign breast diseases are common among young females. Most of them present as painless mobile breast lump. Breast pain and nipple discharge are the other symptoms. Fibroadenoma is the commonest in our study, followed by fibrocystic changes Clinical diagnosis was correlated with cytology and histopathology.